Optical Bullets Using Two Integration Architectures - Ja'afar Mohamad Jawad, Anwar; Biswas, Anjan; Yildirim, Yakup; Saleh Alshomrani, Ali (Al-Nahrain Journal of Science, 2024)
In this study, the exact Bullet solutions for the (3+1)-dimensional Schrödinger equation which demonstrates the Bullet behaviour in optical fibers can be accumulated through the extended simple equation method, and Csch method. The applied strategies may retrieve several kinds of optical Bullet solutions within one frame, which is quite simple and reliable. As a result, we are able to develop a variety of traveling wave structures namely the periodic, singular Bullet wave. The extended simple equation method, and Csch method approaches were implemented perfectly and can be extended to deal with many advanced models in contemporary areas of science and engineering.